Management of Date Palm Pests: Lack of Commercial Input. (1st February 2022) - Ansari, Minshad; Harding, Sarah
According to Statista, the global date market was valued at about 13.4 billion in 2019 and is forecast to reach 16.25 billion by 2025. However, this valuable crop is threatened by numerous pests. In fact, the date palm is associated with 132 species of insect and mite pests, which feed on the leaves, roots, trunk, and fruits on the palm, as well as stored dates. The most economically important pests include the red palm weevil, (Rhynchophorus ferrugineus), old world date mite (Oligonychus afrasiaticus), lesser date moth (Batrachedra amydraula), Dubas date bug (Ommatissus lybicus), green pit scale (Palmaspis phoenicis), carob moth (Ectomyelois ceratoniae), date palm longhorn beetle (Jebusaea hammerschmidti) and almond moth (Cadra castellan). It has been estimated that effective curative approaches for red palm weevil infestations alone could result in savings as high as 104 million. Several research groups are working to find effective solutions to control these pests, but as yet no commercial biocontrol products are registered or available for curative control of the palm beetle and larvae. Therefore, a more robust Integrated Pest Management(IPM) system is needed to reduce the pest damage. Commercial formulations include root treatments, insecticide-based capsules that are injected into the trunk, or foliage/fruit sprays. However, chemical insecticides should not be the only solution to the management of date palm pests, especially those concealed inside the trunk or beneath palm tissues, making them difficult to target. This is primarily because chemical insecticides frequently just kill the target pest's natural enemies, while the pests themselves remain protected within the date palm. Several approaches are used but it has also been shown that resistance against a range of commonly used chemical insecticides (profenophos, imidacloprid, chlorpyrifos, cypermethrin, deltamethrin, spinosad, lambda-cyhalothrin, phosphine) develops after extensive use. Resistance ratios as high as 79-fold have been reported, compared with susceptible control pests. Researchers have reported significantly improved populations of natural enemies of target pests in date palm plantations when chemical insecticide use is reduced. Around 90 species of beneficial predators and parasitoids have so far been reported, suggesting that biological control with microbials could be incorporated into a synchronised IPM programme.